1991
DOI: 10.1002/jsfa.2740560207
|View full text |Cite
|
Sign up to set email alerts
|

Combination of mass spectrometry and site‐specific NMR isotope analyses in the characterisation of amino acids

Abstract: Experimental strategies have been developed which make amino acid probes accessible to the N M R study of site-specijir natural isotope fractionation.A multi-isotope approach, based on combined mass spectrometry determination of hydrogen-, carbon-and nitrogen-overall

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(24 reference statements)
1
7
1
Order By: Relevance
“…Taking into account the origin of the atoms in both arginine and ornithine and the symmetry of putrescine, the methylene sites 8, 12 and 10, 11 of the pyrrolidine ring of nicotine are supposed to arise from the C3 and C4 methylenic groups of glutamic acid (50% each). In this respect, an investigation of the distribution of deuterium in glutamic acid by the SNIF-NMR method (Vallet et al 1991) has shown that relatively wide ranges of variation are exhibited by the site-specific hydrogen isotope ratios. Sites 6 and 5,7 of nicotine arise from C2 or C4 atoms of ornithine or arginine.…”
Section: Deuterium Distribution In the Nicotine Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the origin of the atoms in both arginine and ornithine and the symmetry of putrescine, the methylene sites 8, 12 and 10, 11 of the pyrrolidine ring of nicotine are supposed to arise from the C3 and C4 methylenic groups of glutamic acid (50% each). In this respect, an investigation of the distribution of deuterium in glutamic acid by the SNIF-NMR method (Vallet et al 1991) has shown that relatively wide ranges of variation are exhibited by the site-specific hydrogen isotope ratios. Sites 6 and 5,7 of nicotine arise from C2 or C4 atoms of ornithine or arginine.…”
Section: Deuterium Distribution In the Nicotine Moleculementioning
confidence: 99%
“…In this respect, an investigation of the distribution of deuterium in glutamic acid by the SNIF-NMR method (Vallet et al 1991) has shown that relatively wide ranges of variation are exhibited by the site-specific hydrogen isotope ratios. Sites 6 and 5,7 of nicotine arise from C2 or C4 atoms of ornithine or arginine.…”
Section: Deuterium Distribution In the Nicotine Moleculementioning
confidence: 99%
“…Approximately 10 mg of freeze-dried leaf material was weighed into tin capsules, which were sealed and placed inside a zero-blank autosampler attached to a Costech Elemental Analyzer ECS4010 (Costech International). Samples were analyzed according to Vallet et al (1991).…”
mentioning
confidence: 99%
“…NMR/MS experiments on the analysis of site-specific natural isotope fractionation after combustion or preparation in a glove box under anhydrous nitrogen atmosphere are described [348]. This "multi-isotopic approach" is proposed for origin identification of plant and other samples.…”
Section: Analytical Systemsmentioning
confidence: 99%
“…The NMR technique was used in humus research [ 120, 336, 3371, fertilizer transformation experiments [3 11, ammonia fixation studies [337], metabolic studies in vivo [7,8,105,3601, monitoring routes for nitrogen assimilation [63], and studying site-specific natural isotope fractionation of amino acids [348].…”
Section: "N Measurementsmentioning
confidence: 99%